2008
DOI: 10.1080/14733140802055011
|View full text |Cite
|
Sign up to set email alerts
|

Online counselling: The experience of counsellors providing synchronous single‐session counselling to young people

Abstract: Kids Help Line (KHL) is a national Australian youth counselling service that provides free online and telephone counselling. This qualitative study examines the experience of 26 online KHL counsellors. Using a focus group methodology, counsellor responses were organised into categories: privacy and an emotionally safe environment; communication through text; and time. Counsellors reported the main benefit of the online environment to be emotional safety, due to reduced client emotional proximity to the counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 10 publications
5
98
0
9
Order By: Relevance
“…Specifically, they report that therapeutic relationships can be more convenient and feel safer when working online with young people (e.g. Bambling, King, Reid, & Wegner, 2008;Dowling & Rickwood, 2016;Glasheen, Campbell, & Shochet, 2013).…”
Section: Developing Accessible Counselling For Studentsmentioning
confidence: 99%
“…Specifically, they report that therapeutic relationships can be more convenient and feel safer when working online with young people (e.g. Bambling, King, Reid, & Wegner, 2008;Dowling & Rickwood, 2016;Glasheen, Campbell, & Shochet, 2013).…”
Section: Developing Accessible Counselling For Studentsmentioning
confidence: 99%
“…Bambling, King, Reid, and Wegner showed that when emotions were displayed at a lower level of intensity, psychotherapists underestimated the severity of the client's problems during a text-based, synchronous, single-session of counseling [29]. Given this information, the current study sought to examine the relationship between the emotionality of therapeutic communication and decision-making when communication technologies are employed.…”
Section: The Current Studymentioning
confidence: 99%
“…Counselors who are used to working in face-to-face counseling settings report that they find it difficult to establish the same type of rapport and provide the same levels of emotional support for clients without access to visible and audible cues (Bambling et al 2008;Danby et al 2009;Mallen, Vogel, Rochlen, and Day 2005). Ellerman-Bull (2003: 62) indicates that a significant challenge for counselors who wish to provide online counseling services is "reinBrought to you by | University of Queensland -UQ Library Authenticated Download Date | 12/14/15 4:29 AM terpreting counselling theories and frameworks in the absence of voice or body language."…”
Section: Online Counselingmentioning
confidence: 99%
“…Debates within the literature often center on the differences between online and face-to-face approaches to counseling, and often are described from the perspectives of the counselors (i.e., Bambling et al 2008;Fenichel et al 2002;Griffiths 2005;Griffiths and Cooper 2003;Hanley 2006;Hunt 2002;Yager 2003). Counselors who are used to working in face-to-face counseling settings report that they find it difficult to establish the same type of rapport and provide the same levels of emotional support for clients without access to visible and audible cues (Bambling et al 2008;Danby et al 2009;Mallen, Vogel, Rochlen, and Day 2005).…”
Section: Online Counselingmentioning
confidence: 99%